2014
DOI: 10.1109/tmech.2013.2242482
|View full text |Cite
|
Sign up to set email alerts
|

Damping and Tracking Control Schemes for Nanopositioning

Abstract: Fast and accurate tracking of periodic reference trajectories is highly desirable in many nanopositioning applications, including scanning probe microscopy. Performance in common positioning stage designs is limited by the presence of lightly damped resonances, and actuator nonlinearities such as hysteresis and creep. To improve the tracking performance in such systems, several damping and tracking control schemes have been presented in the literature. In this paper, five different control schemes are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…A simple, effective, and robust damping and tracking control law for a lightly damped structure can be obtained by modifying and optimally tuning an integral control law (Eielsen et al, 2014). Since the BBD is a sampled device, reconstruction and anti-aliasing filters must be present in order to mitigate aliasing effects.…”
Section: Modified Integral Control Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple, effective, and robust damping and tracking control law for a lightly damped structure can be obtained by modifying and optimally tuning an integral control law (Eielsen et al, 2014). Since the BBD is a sampled device, reconstruction and anti-aliasing filters must be present in order to mitigate aliasing effects.…”
Section: Modified Integral Control Lawmentioning
confidence: 99%
“…As discussed in (Eielsen et al, 2014), the optimal values for the cut-off frequency and the integral gain can be found by minimizing…”
Section: Modified Integral Control Lawmentioning
confidence: 99%
“…However, numerous works have shown, experimentally, that integral tracking control reduces the effects of hysteresis on positioning error (Bhikkaji et al, 2007;Aphale et al, 2008a;Fleming, 2010). Eielsen et al (2014) showed that using Model Reference Control to obtain a closed-loop Butterworth filter pattern provides increased performance over traditional damping and tracking controllers, in terms of bandwidth and positioning error. The aim of this work is to provide a quick and simple method of deriving controllers to obtain a closed-loop Butterworth filter pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects can be effectively compensated for such as hysteresis (Eielsen et al, 2012;Kaizuka and Siu, 1988;Croft et al, 2001). To handle the resonant peaks of the lightly-damped vibration dynamics, simpler control schemes such as damping and tracking control can be employed (Eielsen et al, 2013;Aphale et al, 2008;Fleming, 2010;Fleming et al, 2010). However, higher order model-matching based techniques, such as model reference control (MRC), linear quadratic control (LQR) and H ∞ -control, can in principle allow for higher bandwidth, and can therefore lead to better tracking performance.…”
Section: Introductionmentioning
confidence: 99%